Pengembangan Modul Berbantu Flipbook Maker Sebagai Sumber Praktikum Fisika Kelas X Berbasis Android (Powerpoint) - Isti Luthfiani; Kresensia Maria Dua; Mia Yunita Sari; Rizka Mukhzalifah (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Nowadays technology has become a loyal friend in everyday life almost every hour, minute and even second of humans can not be separated from the name technology. The practicum modules presented by educational institutions still seem monotonous or less varied. To overcome the problems experienced by these students, it is necessary to use learning media that utilizes technological developments so that current learning media can be packaged in an attractive way, one of which is by making learning media in the form of an Android-based flipbook maker assisted module application (powerpoint). Almost all students have smartphones, because smartphones provide so much entertainment for their users so this can be used to support the learning process, so the use of smartphones can also be useful in improving the quality of education and achieving goals in education. The application in this study contains a cover, introduction, material, video and bibliography. This research method uses a type of research method in the form of research and development methods using the ADDIE development model, namely Analysis, Design, Development / Development, Implementation and Evaluation, the research objective is only to develop and test the feasibility of learning media applications based on validator assessment. The data collection instrument consisted of a material expert validation sheet and a media expert validation sheet given to 2 (two) validators. This study shows the results of the assessment of media experts reached 86.11% with a very good category and also the assessment of material experts reached 84% with a good category. Based on the results of research and discussion of the learning media, this physics practicum module is feasible to be used and tested for students.